Application of linear approximate almost ideal demand system model to studying food consumption patterns in Malaysia - Ooi, Bee Chen (2016)
With growing income, consumption of food in Malaysia has shifted from starchy staples towards livestock products, wheat, seafood, vegetables, and fruits. This has been powered by a rise in the populace of Malaysia and its purchasing power, which puts the focus on understanding the consumption patterns in this country. The food requirement is guided by the consumption patterns. This study aims to quantify the impact of a family’s socio-demographic characteristics in terms of outlay on 11 food groups in Malaysia by employing LES model, and the projection in food consumption patterns in term of the income elasticity, compensated and uncompensated own-price elasticity by employing the LA/AIDS model. The results are utilised to estimate prospective consumption of food up to the year 2025. The study utilised data from the Household Expenditure Survey (HES) 2009/2010, conducted by the Department of Statistics, Malaysia. A total of 21077 samples were obtained. The study relies primarily on the descriptive as well as econometric analysis of the most recent. The projection is carried out by employing the Statistical Analysis System (SAS) program, and through the application of the Iterative Seemingly Unrelated Regression (ITSUR) process. The Full Information Maximum Likelihood (FIML) method was employed to project the demand model. More than 50 percent of the parameter estimates in every equation system in this study are statistically significant, and the model specification is appropriate. The projection outcomes signify that families exhibit a significantly rising food consumption with higher income at a 1% significance level. The sign and scale of the elasticities show that cereal, rice, fruits, oil, vegetables, sugar and other food are ‘necessities to price change’ among families in Malaysia. Likewise, fish, cereal, milk, vegetables and other foods tend to be ‘luxurious to income change’. Notably, ownprice elasticities for fish, meat, and other food are quite elastic with change in price. This signifies the behaviour of Malaysian customers correctly, and if fish, meat and other food products are imported, it could bring down the prices, benefitting sellers as well as consumers. The income elasticity is more pronounced in rural areas than urban regions. Usually, the income elasticities for 11 food items, with the exception of other foods, are comparatively high in the LA/AIDS model in comparison to the Tobit model. This is because, given the economic scenario in Malaysia, several poor families are dealing with tight budgetary limits. Moreover, all chosen food commodity groups are termed as very essential items as they cater to the basic needs of people. Outlays on all commodities are considerably driven by the income of the household. Furthermore, size of the family, the reference person’s age, and gender of the head of family are crucial variables which would affect the purchase decisions. In terms of estimated food consumption until the year 2025, self-sufficiency in food may unlikely be achieved for Malaysia. Over the period of estimation, the percentage of cereal consumption is likely to be higher compared to rice products in 2020 and 2025. There would be a downhill trend in the consumption of fish, rice, and vegetables, and an upward trend for meat, cereal, and fruits for the next 10 to 15 years, as against the base year 2010. Lastly, our findings imply that income-focused policies are vital for attaining better nutrition and diminish the issue of unbalanced diets in Malaysia. The country would have to raise its production of food and enhance its food distribution systems to ensure enough supply for its burgeoning populace.